2016
DOI: 10.1097/brs.0000000000001542
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to the Surgeon and Patient During a Fluoroscopic Procedure

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Therefore, exposure to radiation can be reduced by positioning physicians farther away from the C-arm fluoroscope and patient. It is recommended that pain physicians perform procedures on the side of the image receptor not the side of the X-ray tube while checking lateral fluoroscopy, and that they should keep their hands away from the irradiated area [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exposure to radiation can be reduced by positioning physicians farther away from the C-arm fluoroscope and patient. It is recommended that pain physicians perform procedures on the side of the image receptor not the side of the X-ray tube while checking lateral fluoroscopy, and that they should keep their hands away from the irradiated area [15]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Multiple studies have introduced more advanced fluoroscopy devices to assist an orthopedic surgery, and numerous strategies protection has been proposed to minimize the radiation exposure. [ 27 33 ] Lee et al [ 1 ] indicated that following factors could reduce radiation exposure during intraoperative use of C-arm, which included distance from the patient, C-arm configuration, radio-protective equipment, rotating the surgeons’ eyes away from the patient, and avoiding direct exposure of surgeons’ hands. Yu and Khan [ 31 ] found that orthopedic surgeons can decline potential radiation risks by optimizing variables such as the use of barriers, knowledge of position, distance from the radiation source, and use of advanced image guidance navigation-assisted technology.…”
Section: Discussionmentioning
confidence: 99%
“…The fluoroscopically guided technique has provided effective assistance for orthopedic surgery, whose drawback appears to dramatically increase radiation exposure to surgeons as well as other medical staff. [ 1 ] Orthopedic surgeons can be exposed to primary radiation and secondary radiation from iatrogenic X-ray. Primary radiation refers to direct radiation exposure while a surgeon enters the space between x-ray generator and receptor, and secondary radiation mainly refers to scattered radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the surgeon’s hands, thyroid gland, and eyes receive obvious exposure to radiation 15 - 19 . We previously reported on the measurement of radiation with use of cadavers, and the results of that study showed that the measurement of radiation was valid and reproducible 20 .…”
mentioning
confidence: 97%